What Are the Applications of AI in Long-Term Care? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2021)
The integration of artificial intelligence (AI) into the healthcare sector has been a transformative force, and its impact on long-term care is becoming incr...
Keywords: AI in Geriatrics; Applications; Long-Term; Care; Artificial Intelligence; Healthcare